”HVER GANG JEG SKRIVER EN ROMAN” – METAFIKTIVE FORMER OG INDSTILLINGER I INGER CHRISTENSENS AZORNO - Gregersen, Sune (Folia Scandinavica Posnaniensia, 2017)
The paper presents an analysis and discussion of the Danish writer Inger Christensen’s experimental novel Azorno from 1967. It is argued that the novel, which is partly in epistolary form, can be read as a literary objet trouvé, a found manuscript consisting of a struggling writer’s unfinished notes and documents. I then attempt to characterise the novel using the typology of metafictional forms and attitudes proposed by Gemzøe (2001), and point out a number of potential problems with this typology.